Economic Growth : The Impact of Zakat Funds and Tax on Business Capital - Anggadini, Sri Dewi; Surtikanti, Surtikanti; Hassan, Faez M. (IKONOMIKA, 2020)
This study aims to determine the effect of Zakat Funds and Tax on Business Capitales on Economic Growth. The population in this study is the data of the Province of West Java from 2010 to 2017 where the economic growth report, Tax on Business Capital report and zakat fund distribution report are used.   The sample taken by the author in this study is the Zakat Fund Distribution Data, Tax on Business Capital Data and the Gross Regional Domestic Product (PDRB) data of West Java Province from 2010 to 2017. Researchers used multiple statistical analysis and correlation methods. To obtain more accurate results in multiple regression analysis, classic assumption testing is executed so that the results obtained are regression equations. The results of the study show that the Zakat Fund Distribution and Tax on Business Capital data have a significant effect on economic growth. Based on data processing, it shows that the distribution of zakat funds and local taxes simultaneously in providing an influence on economic growth variables of 76%. While the rest of 100% - 76% = another 24%  is the influence of other variables not examined in this study.Keywords : Zakat Funds; Tax on Business Capital; Economic Growth